Temperature and Cardiovascular Morbidity - Harikrishna Halaharvi; Paul J. Schramm, MS, MPH; Ambarish Vaidyanathan, PhD (The ASEAN Journal of Military and Preventive Medicine, 2024)
The negative influence of extreme heat on cardiovascular health has been observed across various geographical locations across the world. In the state of New York, discovered a significant increase in cardiovascular disease (CVD) related emergency department, following an extremely hot day. Increase in 3-day delayed CVD hospital admissions with every 1°C above the temperature-health effect curve (29°C–36°C). Another study conducted in China, estimated that the cumulative relative risk of having an out-of-hospital cardiac arrest (OHCA) following a day with extreme heat. Analogous impacts of extreme heat on cardiovascular morbidity have also been observed in Australia and Korea. Data from Thai Nguyen province in Vietnam with the daily weather, observed no statistically significant association between hot temperatures and CVD-related hospital admission over the course of lag days 0–30. Contradictory evidence was also found in epidemiological studies conducted across Europe. A systematic review and meta-analysis of twenty-one studies also failed to detect a significant association between cardiovascular morbidity and ambient temperature.